Comparison of primary patency of radiocephalic and brachiocephalic arteriovenous fistula in East Borneo, Indonesia - Gratianus Billy Himawan; David Hermawan Christian (Indonesian Vascular Access Association (IVAA), 2022)
Background: There is still very limited study available for patency of arteriovenous fistulas (AVF) from developing country, specifically in East Borneo, Indonesia. The aim of this study is to compare the primary patency rate between radiocephalic (RC) and brachiocephalic (BC) AVF and to analyze the risk factors involved in the primary patency results of AVF RC and BC for hemodialysis. Methods: This study is a retrospective cohort study with a total of 154 patients underwent AVF from February 2017 until august 2018 and were monitored until august 2019. The patient’s primary patency of AVF was evaluated by the Kaplan-Meier survival curve. Each of the risk factors that were predicted to influence patency was analyzed for each AVF. Result: The mean age of 154 patients was 52.9 ± 9.5 years old. RC AVF was made in 130 patients (84.4%) and BC AVF was made in 24 patients (15.6%). There was no significant difference between the estimated primary patency for the RC group and BC AVF, the log-rank test (p=0.15). Risk factors for age, gender, hypertension, DM, and frequency of hemodialysis in both AVF showed statistically insignificant for primary patency. Conclusion: Our study showed there was no significant difference in the primary patency rate between the RC AVF and BC AVF group and other risk factors not significantly affecting primary patency in either type of AVF.